Estudo preliminar sobre potenciais cognitivos em tarefa de tomada de decisão social - Campanhã, Camila (2010)
Decisions engage careful consideration of the risks and benefits involved in a particular choice. As we live in society, these choices are not only related to our personal interests. Therefore, social interaction has an important role, because the other is part of the context in which we evaluate decisions. Previous studies show the importance of trust and empathy in decision-making processes. In fact, Boudreau, McCubbins and Coulson (2009) showed that trust in another person interferes with behavioral response and also in event related potentials recorded during the test. However, as in other studies, trust was studied by the instruction given to participants that they will base their choices by reports made by another human being - unknown person. The use of an unknown person limits the interpretation of the role of trust involved in decision making processes. Thus this study aims to investigate the decision making processes in a task in which the participant brought to the lab a person (a trusted friend) that act as reporter. In addition, there are few studies investigating event-related potentials in tasks of social decision. Therefore, this study aim to understand the role of trust in decision-making by analysis of behavioral performance in an adapted version of the Ultimatum Game task and also investigate the event related potentials collected simultaneously. Among the main findings, we found a change in the perception of fairness (in fact there was no difference) and, consequently, a change in decision-making with more acceptance of proposals on the condition of interaction with the trusted person than other proposers. Moreover, the P3, FN and LPC potential were modulated by the impact of trust, and by moral internalization, and differed between genders. This study may increase knowledge about the neurobiological bases of behavior and decision making processes involving social interaction, trust and empathy.